Psychological peculiarities of self-determination of Ukrainian-speaking and Russian-speaking youth in ethnic context - Kakusha, Lina (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
This article presents an empirical study of psychological peculiarities of self-determination of students in the ethnic context depending on the linguistic factor. Analyzed components of social identity and the place Ethnic identity in its structure. Reveals the emotional value component of ethnic auto and hetero stereotype on "typical Ukrainian" and "typical Russian". The level of ethnic identification, targeting ethnic preferences of students.
Keywords: self-determination of students; ethnic identification; auto- and hetero-stereotypes